PENGARUH MANAJEMEN LABA, TAX AVOIDANCE, DAN PROFITABILITAS PADA NILAI PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN PERBANKAN INDEKS LQ45) - Noor Afifah; Mona Adriana P (Pusat Riset dan Inovasi Nasional, 2023)
This puspose of this tudy to determine the effect of earnings management, tax avoidance, and profitability on firm value. This type type of research is quantitative. The study was conducted on banking companies listed index LQ45 on the Indonesia Stock Exchange in 2015-2021, with a total sample of 35 samples using a purposive sampling method. Data collection methods are secondary data. The analysis was done by using panel data method. Earnings management is measured using price to book value (PBV), tax avoidance is measured using an effective tax ratio (ETR), and profitability is measured using an return on asset (ROA). The results of this study indicate that (1) earnings management has a positive on firm value. (2) tax avoidance has a positive on firm value. (3) profitability has a positive on firm value.